2016
DOI: 10.1371/journal.pone.0152260
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Price and Socio-Economic Level on the Consumption of Sugar-Sweetened Beverages (SSB): The Case of Ecuador

Abstract: The objective of this article is to estimate the own-price, cross-price and income elasticities of demand for SSB in Ecuador, as an indispensable step for predicting a reduction in the consumption of said beverages caused by the potential implementation of taxes in Ecuador. In addition, the own-price, cross-price and income elasticities of sugar-free substitutes like mineral water and diet soft drinks and juices are also estimated. The data from the 2011–2012 ENIGHUR, which contains detailed information on hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 17 publications
11
55
2
5
Order By: Relevance
“…In particular, the proposed tax could lead to a reduction of soft drink consumption by 11.4%. This is in line with previous studies in Mexico by Colchero et al (2015) [11], in Guatemala by Chacon et al (2018) [23], and in Ecuador by Paraje (2016) [24], where the own-price elasticity of SSB are estimated at 1.16, 1.39, and 1.17-1.33, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the proposed tax could lead to a reduction of soft drink consumption by 11.4%. This is in line with previous studies in Mexico by Colchero et al (2015) [11], in Guatemala by Chacon et al (2018) [23], and in Ecuador by Paraje (2016) [24], where the own-price elasticity of SSB are estimated at 1.16, 1.39, and 1.17-1.33, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In general, studies show that SSBs are price-elastic, meaning that consumptions drops more than proportionally to price increases. Recent studies for Mexico and Ecuador report price-elasticities of −1.16 and −1.2 respectively (Colchero, Salgado, Unar-Munguía, Hernández-Ávila, & Rivera-Dommarco, 2015; Paraje, 2016). In contrast, evidence on price-elasticity for energy-dense processed foods is less conclusive, mainly because there is a lack of consensus regarding the definition of ‘junk’ food.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to contradict the findings of several other studies that have investigated the impact of SSB taxes on different income groups. Studies regarding price elasticities have determined lower income households to have a greater sensitivity to price30–32 41 42 and therefore are assumed to decrease consumption of SSBs proportionally more in response to a tax. Modelling studies from high-income countries have shown greater reductions for lower income groups 41 42.…”
Section: Discussionmentioning
confidence: 99%
“…Own-price and cross-price elasticities for each beverage category (carbonated soft drinks, milk, diet drinks, fruit juice) for each income quintile were estimated from published international sources, as Indonesian estimates were not available 30–34. Own-price elasticity estimates were derived from demand system analyses for Mexico (73 311 households), Ecuador (38 234 households) and New Zealand (6028 households) (table 1).…”
Section: Methodsmentioning
confidence: 99%